Total protein, Fe and Zn analysis (Total and in Vitro) of fortified and fermented Cassava (Manihot esculenta Crantz) flour. - Eulogio, Tarhata May Luningning Hiponia
Protein-energy malnutrition is the most lethal form of malnutrition and is usually prevalent in regions where people often rely upon starchy staple, is an excellent anergy source of nutritive value because of its highly digestible carbohydrates., Due to its low protein content of 1-2 percent, cassava roots were (1) fortified with soya in a 1:2 and 1:4 and (2) fermented (3 to 6 days) to enhance its nutritive value. Protein content was monitored through Bradfort standard asssay while total mineral was done using the wet digestion method. In vitro mineral analyses were also carried out to determine the effectiveness of fortification with soya and the fermentation in enhancing the nutritive value of cassava. Only Fe and Zn were analyzed for total and in vitro mineral analysis. Results of the three analyses revealed a correlation between total protein and total Fe. Among the treatments, it is the soya fortified sample in the 1:2 ratio, SF (1:2), that most enhances the nutritive value of cassava in terms of increase in protein, total Fe and Zn, and in vitro Fe and Zn. The order of the increase in the protein content of the amples is FU3 < FU6 < SF (1:4) < SF(1:2). The values are 33.33 percent , 86.96 percent, 88.89 percent and 92.31 percent, respectively. compared to teh control, statistics show that SF(1:2) give a significant increase in all analyses except in the determination of total Zn in which the amount of Zn is only 1.81 percent higher compared to the control.